Human induced pluripotent stem cell line (PNUSCRi005-A) generated from severe type of Hunter syndrome patient carrying exonic deletion (exon 4–7 del) in in human iduronate 2-sulfatase gene - Nayeon Lee; Haneul Noh; Chong Kun Cheon (Stem Cell Research)
Mucopolysaccharidosis Type Ⅱ, as Known as Hunter syndrome, is a rare X-liked genetic disease caused by mutations in iduronate-2-sulfatase (IDS) gene. We obtained peripheral blood mononuclear cells (PBMCs) from a patient with a severe type of Hunter syndrome carrying c.418 + 495_1006 + 1304 deletion in the IDS gene. We generated an induced pluripotent stem cell (iPSC) line (PNUSCRi005-A hiPSCs) from the PBMCs of the patient using non-integrative Sendai virus. The hiPSCs exhibited embryonic stem cell-like characteristics, showed differentiation properties into three germ layers, and had a normal karyotype.